The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fmars.2021.791484
|View full text |Cite
|
Sign up to set email alerts
|

Precautionary Principle or Evidence-Based Conservation? Assessing the Information Content of Threat Data for the Yangtze Finless Porpoise

Abstract: Conservation management requires evidence, but robust data on key parameters such as threats are often unavailable. Conservation-relevant insights might be available within datasets collected for other reasons, making it important to determine the information content of available data for threatened species and identify remaining data-gaps before investing time and resources in novel data collection. The Yangtze finless porpoise (Neophocaena asiaeorientalis asiaeorientalis) has declined severely across the mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 71 publications
(105 reference statements)
0
6
0
Order By: Relevance
“…Analysis of porpoise mortality data obtained through interviews with artisanal fishers by Turvey et al (2013) suggested that bycatch mortality has decreased over time, and might therefore merely be tracking rather than driving population decline. Mogensen et al (2022) also found limited spatial correlation between observed porpoise deaths and fishing activity patterns at multiple spatial scales, but population modeling suggested that reported bycatch mortality might exceed sustainable levels. The dynamics of how bycatch and other potential threats act and interact across the different multi-threat landscapes of the Yangtze system, their specific relationships with porpoises (e.g., levels and patterns of spatial overlap), and how these might vary at different scales across time and space, remain poorly understood.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Analysis of porpoise mortality data obtained through interviews with artisanal fishers by Turvey et al (2013) suggested that bycatch mortality has decreased over time, and might therefore merely be tracking rather than driving population decline. Mogensen et al (2022) also found limited spatial correlation between observed porpoise deaths and fishing activity patterns at multiple spatial scales, but population modeling suggested that reported bycatch mortality might exceed sustainable levels. The dynamics of how bycatch and other potential threats act and interact across the different multi-threat landscapes of the Yangtze system, their specific relationships with porpoises (e.g., levels and patterns of spatial overlap), and how these might vary at different scales across time and space, remain poorly understood.…”
Section: Introductionmentioning
confidence: 92%
“…Furthermore, our data cannot in themselves indicate whether bycatch is a more serious or significant threat than sand-mining or other uninvestigated anthropogenic pressures, necessitating further research into the dynamics of humanenvironmental relationships within this system. In particular, additional research is required into individual-level and population-level effects on porpoises of other vessel traffic, other sources of anthropogenic noise and habitat alteration, and pollutants known to affect cetacean reproductive success and survivorship, all of which remain poorly understood in the Yangtze (Mei et al, 2021;Mogensen et al, 2022). We encourage future investigation to determine multi-scale relationships between porpoises, threats, and biotic and abiotic environmental variables that might regulate porpoise habitat use, along with investigation of additional anthropogenic activities, to work towards establishing a more nuanced understanding of the sustainability of different threats to porpoises.…”
Section: Conservation Recommendationsmentioning
confidence: 99%
“…An example is the Yangtze River dolphin ( Lipotes vexillifer ) which was brought to extinction as a result of incidental capture in fisheries [ 28 ]. Currently, the vaquita ( Phocoena sinus ) [ 29 ] and the Yangtze finless porpoise ( Neophocaena asiaeorientalis asiaeorientalis ) [ 30 ] are in the same fate if no immediate conservation measures are taken. Accidental entanglement of the Mediterranean monk seal on fishing gear due to depredation has been reported in Greek fisheries and has been identified to be among the main causes of the species’ mortality [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the main cause(s) of unsustainable porpoise mortality are unclear. Robust evidence remains lacking to suggest a primary role of fisheries interactions in driving porpoise decline, and Yangtze fisheries restrictions represent a precautionary conservation approach for porpoises (Mogensen et al, 2022). Indeed, other factors (e.g.…”
Section: Introductionmentioning
confidence: 99%